Reasons for placement decisions in a case of suspected child abuse: The role of reasoning, work experience and attitudes in decision-making. (September 2018) - Bartelink, Cora; Knorth, Erik J.; López López, Mónica; Koopmans, Carien; ten Berge, Ingrid J.; Witteman, Cilia L.M.; van Yperen, Tom A.
Abstract: Child welfare and child protection workers regularly make placement decisions in child abuse cases, but how they reach these decisions is not well understood. This study focuses on workers' rationales. The aim was to investigate the kinds of arguments provided in placement decisions and whether these arguments were predictors for the decision, in addition to the decision-makers' risk assessment, work experience and attitudes towards placement. The sample consisted of 214 professionals and 381 students from the Netherlands. The participants were presented with a vignette describing a case of alleged child abuse and were asked to determine whether the abuse was substantiated, to assess risks and to recommend an intervention. The participants' placement attitudes were assessed using a structured questionnaire. We found that the participants provided a wide range of arguments, but that core arguments – such as the suspected abuse, parenting and parent-child interaction – were often missing. Regression analyses showed that the higher the perceived danger to the child and the more positive the participants' attitudes towards placement, the more likely the participants would be to propose placing the child in care. Arguments related to the severity of the problems (i.e., suspected abuse, parenting and the child's development) as well as the parents' perceived cooperation also influenced placement decisions. The findings indicate trends in the decision-making process, in the sense that participants who decided to place the child out-of-home emphasized different arguments and had different attitudes towards out-of-home placement than those who did not. We discuss the implications of our findings.